NONISOLATED FORMS OF RATIONAL TRIPLE POINT SINGULARITIES OF SURFACES AND THEIR RESOLUTIONS - Sharland, A. Altintas; Cevik, G.; Tosun, M. (ROCKY MT MATH CONSORTIUM, 2016)
We give a list of nonisolated hypersurface singularities of which normalizations are the rational triple point singularities of surfaces and construct their minimal resolution graphs by a method introduced by Oka for isolated complete intersection singularities. We also show that nonisolated forms of rational triple point singularities and their normalizations are both Newton non-degenerate.
Keywords: Rational singularities; nonisolated hypersurfaces; Newton polygon; resolution graphs; ALGEBRAIC VARIETY; GEOMETRY; FIELD; Mathematics